Perancangan Instalasi Interaktif Komposisi Musik dan Visual (Studi Kasus: Tari Saman) - Grace Caroline Sahertian; Hendy Hertiasa; Ary Setijadi Prihatmanto (JURNAL RUPA, 2017)
On such era of globalization, we canâ€™t only focus on utilization of technological advances, we also have to look on the implementation and development of technological advances itself. Creativity of each individual is a basis in the birth of new innovations if supported by the proper technology. We expected the merger of technology and creativity, along with the local culture will be able to maintain the values and integrity of Indonesian national identity. As a case study, â€œInteractive Installation Design of Music and Visual Composition From Saman Danceâ€ is one attempt to realize the above ideas. The result of the design of this interactive installation is a game tool for composing music and visual. Different from the pre-existing games, on this game the user is the one who controls the system, not the opposite.